(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: Idioms are a natural component of language, adding rich cultural context and vivid imagery to communication. These are statements whose meanings are not always connected to the words' literal meanings. To say someone "kicked the bucket" in English does not imply that they actually kicked a bucket; rather, it indicates that they passed away. These vibrant expressions frequently have profound cultural meaning, yet they pose particular difficulties when translating idioms between languages .Idioms' meanings are frequently strongly ingrained in the society from which they come, making translation one of the most difficult tasks. Translation can be challenging, if not impossible, when an idiom in one language lacks a corresponding equivalent in another. For example, many languages lack a literal translation for the English phrase "to let the cat out of the bag," which means to inadvertently divulge a secret.